Effective lecturing skills in English workshop for lecturers of Diploma in Architecture and Site Supervision / Nazima Versay Kudus - Kudus, Nazima Versay (Academy of Language Studies, 2023)
The objective of the workshop is to equip the participants' English language competency skills in view of IKM courses being upgraded from certificate to the diploma level. Madam Nazima Versay Kudus was appointed the head of the project along with other team members which included Mr Noor Azli Affendy Lee, Madam Wan Noorli Razali and Madam Nur Afiqah Ab Latif. It was a 2-day workshop which was held at the Park Avenue Hotel, Sungai Petani from September 20-22, 2022. Various aspects were focused in the workshop. Madam Wan Noorli's session was concentrated on 'Ice Breaking' and 'Giving Feedbacks' meanwhile Madam Nazima's session was directed towards 'Teaching Styles' and 'Delivery Techniques'. The other two consultants namely Mr Azli and Madam Nur Afiqah were entrusted to speak on 'Using Visual Aids and Constructing Tests' and 'Essential Academic Grammar and Facilitating Student Note-Taking' respectively.